Recovery of Bacteriophage from Contaminated Chilled and Frozen Samples of Edible West Coast Crabs - DiGirolamo, Rudolph (1973)
Edible West Coast crabs (Cancer magister and C. antennarius) were contaminated with bacteriophage and then held in a chilled or frozen state. Results indicated a significant survival of virus regardless of storage conditions.